455. ESOPHAGOGASTRIC JUNCTION CANCER: A DIFFICULT BORDER: A WORLDWIDE SURVEY ON ONCOLOGICAL AND SURGICAL APPROACH. (24th September 2022) - Leone, Barbara; De Pasqual, Carlo Alberto; Gervasi, Maria Clelia; Zenzaro, Matteo; Turolo, Cecilia; Weindelmayer, Jacopo; Giacopuzzi, Simone; de Manzoni, Giovanni
Abstract: The incidence of esophagogastric junctional adenocarcinoma (EGJ) has been steadily increasing over the last 30 years, especially in Western countries. Surgical and oncological treatment of these malignancies are still debated, in particular in case of true junctional cancer (Siewert type II tumors). The aim of the study is to compare different approaches to EGJ cancers in high volume centers around the world. We administered a survey to 39 international opinion leaders, working in high volume centers, with a minimum of 50 gastrectomies and 20 esophagectomies performed as first operator. The survey was structured in the form of clinical case scenarios, created to focus on different peculiar issues in the management of Siewert type II tumors. The main fields of investigation were the oncological approach of these malignancies (i.e. choice and type of neoadjuvant treatment) and the preferred surgical strategy. Our first finding was that almost 80% of responders would choose a neoadjuvant treatment even in cT2N0 patients, fearing probably the low accuracy of the clinical staging. Secondly, 60% of surgeons would prefer chemotherapy over chemoradiotherapy in locally advanced Siewert II tumors, regardless of histological subtype and nodal diffusion. As for the surgical strategy, we reported a strong preference (75% of responders) for two-field esophagectomy, over three-field esophagectomy (11%) and total extended gastrectomy (14%). However, in case of signet-ring cell carcinoma, up to 20% of surgeons would prefer an extended total gastrectomy, to avoid a distal positive margin. Our survey confirms that the management of Siewert type II tumors is greatly debated, even among experts of the field, and it needs to be tailored on the patient and tumor characteristics. Even so, we observed a trend towards the choice of chemo over chemoradiotherapy for any histological subtype. When operating on Siewert type II tumors, a thoracic approach is considered necessary by most of responders.